URBAN PLANNING STRATEGY FOR HYBRID SETTLEMENTS: MIXED-USE APPROACHES IN KAMPUNG PETEK, SEMARANG - Christanti, Sherley Ika; Wiwit Setyowati; Rm Bambang Setyohadi Kuswarna Putra; Prita Hanaya Gulton; Syarwah Nailah Fara Ramadhani (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
Kampung Melayu Petek in North Semarang serves as case study illustrating how the interplay of cultural hybridity and historical stratification has resulted in a distinctive urban morphology characterized by mixed land uses and multicultural spatial configurations. This research investigates the viability of strategic mixed-use development as an instrumental planning to preserve and augment these hybrid characteristics while simultaneously addressing contemporary urban dilemmas. Objectives: The primary aim of this study is to investigate methodologies for the preservation and enhancement of cultural hybridity and historical layering in Kampung Melayu Petek through strategic mixed-use development initiatives. Methodology and results: This research employs a qualitative case study methodology focused on Kampung Melayu Petek, North Semarang, using field observations, interviews, and document analysis through a qualitative descriptive lens and phenomenological perspective to scrutinize the influence of acculturation on the hybrid multicultural spatial organization and its manifestations. The findings reveal that the coexistence of Arab, Chinese, Javanese, and Malay-Banjar communities has created a distinctive spatial mosaic of shop-houses (ruko), inward-facing courtyards, and adaptable land uses—an organic form of mixed-use urbanism that is increasingly threatened by modernization, infrastructure expansion, and rigid regulatory paradigms. Conclusion, significance, and impact study: This study highlights the promise of culturally-informed mixed-use planning as a sustainable paradigm for heritage-sensitive urban environments, offering a replicable framework for other multicultural settlements in Indonesia.